The role of circadian rhythm in osteoporosis; a review - Tian, Yihao; Ming, Jian (Frontiers in Cell and Developmental Biology, 2022)
Osteoporosis is characterized by a high incidence rate, with significant effects on people's lives. The underlying mechanisms are complex, with no treatments for the condition. Diabetes is a chronic metabolic disease, with a similar impact on people's lives. Characterized by a series of complications, the condition is also complicated by osteoporosis. Recent studies have indicated that melatonin can be used to treat diabetic osteoporosis by promoting osteoblast proliferation and differentiation, and inhibiting osteoclast differentiation. Specifically, in vivo mechanisms are initiated by stabilizing biological rhythms in bone tissue. In healthy organisms, these biological rhythms are present in bone tissue, and are characterized by bone formation during the day, and bone resorption at night. When this rhythm is disrupted, osteoporosis occurs. Thus, taking appropriate medication at different times of the day could produce different effects on osteoporosis rhythms. In this review, we characterized these processes, and provided treatments and management strategies for individuals with diabetic osteoporosis.